The Selangor State Assembly oversight and government accountability - Mohd Rosli, Rozaini; Quddus, S. M. Abdul (2018)
Government choices, decisions and actions impacts the lives of a country’s citizens. It is imperative to ensure that every decision made by the legislative body has the best interest of the citizens at heart. The constitution of Malaysia provides that, apart from the parliament, at the state level, the State Assembly is entrusted to accomplish that duty. The Selangor State Assembly (SSA) is the legislative body that oversees the government of Selangor. The SSA follows the parliamentary model of government. This paper attempts to examine the effectiveness of the SSA oversight in ensuring the Selangor state government accountability in relation to the Talam case. The concept of accountability has two facets – answerability and enforcement. This study is an explorative attempt to describe the effectiveness of the SSA oversight used in ensuring government accountability. Matching internal and external oversights with the different forms of accountability must have high enforcement or sanctions capacity for the oversight mechanisms to be effective. This paper will examine the following research questions: a) What are the mechanisms available to ensure the accountability of the SSA; b) Are the mechanisms in place ensuring the government accountability in Selangor; and c) What are the challenges in ensuring government accountability in Selangor and how they are to be resolved. The data of this research paper would mainly be from secondary sources. The work of Pelizzo and Stapenhurst (2014) in legislative oversight and government accountability will be used as the theoretical guideline of this study. Their conceptual model highlighted that legislature under some conditions (context) can perform efficiently and effectively their oversight function (which also depends on the tools at their disposal). Legislative oversight, if effectively performed, can keep government accountable; a greater accountability can lead to a reduction in the level of corruption. Reduced corruption results in improved economic development and living standards. This study reveals the extent of the SSA legislative oversight effectiveness in ensuring the Selangor state government accountability.